A rare case of meningioma with extracalvarial extension: A Case report - Jolly Sinha,; Vivek Kumar Kankane,; Avdhesh Shukla,; Avinash Sharma, (Asian Journal of Medical Sciences, 2023)
Meningioma is a common primary tumor of the central nervous system. Here, we describe a case of meningioma en plaque with intracranial mass with osteolysis with extracalvarial extension. The patient was a 54 years male who presented to us with a rapidly growing mass in the left frontal region. On magnetic resonance imaging brain, the mass was avid heterogeneously enhancing extra-axial lesion in the left frontal lobe with surrounding cerebrospinal fluid cleft with an erosion of overlying frontal calvaria on the left side with an extracranial component. Simpson’s grade 1 excision was carried out. Histopathology showed a meningothelial meningioma with low tumor cell proliferation but with infiltration into the bone and angioinvasion. The patient was taken for radiotherapy. The patient recovered well in the post-operative period.